(untitled) (Journal of the College of Basic Education, 2022)
This study is an attempt to measure the Iraqi society’s knowledge about swine flu. The study was conducted by distributing special questionnaires randomly to different segments of Iraqi society of both sexes. The study showed that there is a need to increase the scientific awareness of the Iraqi society about swine flu. This study aimed to increase the scientific awareness of the Iraqi society about swine flu.